Atitudes maternas em relacao ao desenvolvimento infantil - Ribeiro dos Santos, Maria Elizabeth; Lemgruber Garcia, Vera (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
In order to verify the possibility of differences between patterns of maternal attitudes in relation to child rearing, a study was done using interviews with a sample of 30 women from the upper socio-economic level whose ages varied from 20 to 35 years, and 30 women, with these same characteristics, from the lower socio-economic level. They were mothers of at least one child older than 12 months. Significant differences were found in important aspects of child development, and these differences were analyzed.